Estimating erosion resistance of vegetated sea dike embankments through in situ experiments - Mozer, Anne; Almström, Björn; Olsson, Pål Axel; Schüttrumpf, Holger (Frontiers in Built Environment, 2025)
Through in situ experiments, this study investigated the erosion resistance of a prototype dike with different vegetation and soil sections built on the Falsterbo peninsula, Sweden. A gravity-driven wave impact simulator was used to simulate waves breaking on the dike. Two sandy soils and three vegetation types (standard grass, biodiverse seed mixture, and hay) were tested for this study. In general, the study showed consistency in the results between the replications and in comparison to former studies. Thus, initially developed for laboratory experiments, the methodology can be transferred to in situ experiments on existing dikes. The study showed comparable results for higher biodiverse vegetation cover and standard grass regarding the resistance to wave impact. The importance of not only root but also soil parameters could be confirmed. A higher resistance was found with higher root densities and lower fine fractions in the soil. Also, a higher forb diversity resulted in larger root densities. Future studies could build on the present findings by conducting a systematic investigation to gain deeper insights into the impact of vegetation and soil properties.